The Potential Swamp Land Development to Support Food Estates Programmes in Central Kalimantan, Indonesia. (March 2022) - Fahmid, Imam Mujahidin; Wahyudi,; Agustian, Adang; Aldillah, Rizma; Gunawan, Endro
The objective of this study is to analyse the potentials, obstacles and socio-economic condition of swamp land development for food estate programmes in Central Kalimantan, Indonesia. The results for qualitative descriptive and quantitative analysis showed there were approximately 33.4 million hectares of swamp land area, 9.5 million of which have the potential for agricultural land, particularly for rice. The rationale of food estate location are a wide area of land availability, with abundant water resources. The main obstacles of land use of swamp land are: (a) low soil pH (acid); (b) low NPK content in the soil; (c) high Al and Fe solubility (toxic); and (d) tidal influence such that during the wet season the land is flooded and during the dry season the land is dry. This research recommends that swamp land development for food estates requires: water management infrastructure rehabilitation, land management, adaptive and potential commodity selection and farmer institution strengthening and facilitation.